The weeding practices of selected academic libraries in Metro Manila - Melgar, Sherryl Anne Jim A. (2009)
Weeding is the practice of discarding, transferring to storage library materials that have excessive copies and that receive little or no usage at all (McGaw, 1956). Though academic libraries shares many problems and issues in deselecting resources, there are still variations in their withdrawal processes due to the different characteristics of the user community they serve and their goals (Evans and Saporano, 2005). In line with this, this study aimed to know the different weeding practices of selected academic libraries in Metro Manila.